Cancer survivors and work issues from the organisational perspective in Singapore. - Lim, Pei Yi. (2012)
With advances in medical technology in current day society, the rate of cancer survivorship has increased continuously. This topic has gathered more and more attention in the media. There has been plenty of literature analysing this topic and providing recommendations for the betterment of cancer survivors’ lives in the Western context. Unfortunately, this topic has yet to be received widely in Singapore, in terms of governmental support and academic attention. There is thus an imminent need to address problems faced by cancer survivors as they embark on their journey back into the workforce and resume their lives.